Perancangan Pengalaman Pengguna pada Aplikasi Pemesanan Jadwal Potong Rambut Barbershop di Kota Gresik dengan menggunakan Metode Human-Centered Design - Muhammad Misbachul Asrori; Agi Putra Kharisma; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Barbershop conditions in the city of Gresik are crowded with customers and cause queues to pile up. The services offered by the barbershop are not optimal, because when you want to cut, you have to convey it to the barber to do the queue. Therefore, the captain is prone to incorrectly calling the queue. The research produced a user experience application design for ordering haircut tables in Gresik City to reduce the number of queues. The research method uses Human Centered Design (HCD) with the stages of user context analysis, user needs analysis, solution design and solution design evaluation. In the solution design evaluation stage, usability tests and user experience questionnaire (UEQ) tests were conducted on 10 clients and 3 supervisors. Customer test results Effectiveness side 88% Efficiency side 0.162 Goals/second Satisfaction side 77 Good category on rating scale B. Administrator test results Effectiveness side 80% Efficiency side 0.136 goals/second Satisfaction side 80 Good category on rating scale B. Customer UEQ score for the attractiveness aspect received a very good category, the aspects of sharpness, efficiency, reliability and motivation received a good category, and the novelty side received an above average category. UEQ management scores for aspects of Attractiveness, Insight, Competence, Motivation, and Novelty get the Good category. The reliability aspect gets a class above average. These results indicate that the solution design is acceptable with a good usability score and a positive user experience with scores in each aspect above average.